3(x-2)-9=0

Simple and best practice solution for 3(x-2)-9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)-9=0 equation:


Simplifying
3(x + -2) + -9 = 0

Reorder the terms:
3(-2 + x) + -9 = 0
(-2 * 3 + x * 3) + -9 = 0
(-6 + 3x) + -9 = 0

Reorder the terms:
-6 + -9 + 3x = 0

Combine like terms: -6 + -9 = -15
-15 + 3x = 0

Solving
-15 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 3x = 0 + 15

Combine like terms: -15 + 15 = 0
0 + 3x = 0 + 15
3x = 0 + 15

Combine like terms: 0 + 15 = 15
3x = 15

Divide each side by '3'.
x = 5

Simplifying
x = 5

See similar equations:

| 2z-3y-8z-1y= | | 2-x=5 | | (5m+2n-4)-(2m-3n-7)= | | 3a+2+1= | | 2(x+7)=(2x+14) | | (4x-11)=(x+6) | | 3x-5x+17=12-(6x+3) | | x(x+1)-3(x+1)= | | 8x^2-4x+2=0 | | 9+2m=-3-4m | | x(x+3)-5(x+3)= | | 45=0.5(6+3) | | -9x=-27 | | 6(k-5)-(2k-4)=7k | | 9(y-7)=8+8y | | 6y+1-2y=8+3y+6 | | -9(n-6)=-8n-9 | | 4y+3y=6y+3 | | -3(4x-6)+8=-12x+26 | | 0.12(y-7)+0.04y=0.20y-0.9 | | 10x^3-8x^2+2x=0 | | 34X-25=18 | | -9(x-8)+2=74 | | 2(4x+7)-5=8x+9 | | -x+3=22 | | 15t^4-2t^2+78=0 | | n/2-9=-5 | | 30=48t-16t^2 | | 3(2x+35)+5(x+1)=u | | (15+9)x(22-5)= | | u/12-8=-8 | | 44=2(3.14) |

Equations solver categories